Assessment of dental caries status among school children aged 9-12 years of Sebha city-Libya by using of dft/ DMFT & SiC indices (Journal of Medical Sciences, 2020)
Aim: To assess the dental caries status among school children aged 9-12years old in Sebha city of Libya. Material and Methods: This cross-sectional study in which a total of 579 schoolchildren (315 were females and 264 were males) aged 9-12 were involved. Trained dentists had examined the subjects to determine dental indices: DMFT (Decayed, Missed & Filled teeth), dft (decayed and filled teeth) and SiC (significant caries index). The mean, standard deviation and P value were used to analyse data. Results: About 85% of participants had dental caries. The general mean DMFT was 1.3, the general mean dft was 2.4.Significant caries index for primary teeth was 5 and for permanent teeth was 3. No significant difference between males and females, however, there were significant differences between means of age groups in both primary and permanent dentition (P < 0.05). Conclusion: The prevalence of dental caries in primary teeth was greater than in permanent teeth. The high SiC scores suggested that there is a subgroup of participants experienced high rates of dental caries and they need special attention from Libyan health authorities. The health authorities should establish school-based dental health programs to reduce the caries prevalence between schoolchildren in the city.